Anal Cancer Screening and Prevention: Summary of Evidence Reviewed for the 2021 Centers for Disease Control and Prevention Sexually Transmitted Infection Guidelines. (13th April 2022) - Barroso, Luis F; Stier, Elizabeth A; Hillman, Richard; Palefsky, Joel
Abstract: In June 2019 the Centers for Disease Control and Prevention (CDC) convened an advisory group to assist in development of the 2021 CDC sexually transmitted infections (STI) guidelines. The advisory group on anal cancer screening and prevention met to formulate key questions in this field. The group examined published literature and abstracts to assess evidence and give recommendations for development of the CDC guidelines. This article summarizes key questions, evidence, recommendations, and areas for further research for the screening, diagnosis, and prevention of anal cancer.